Functional relationship between subfrnical organ cholinergic stimulation and nitrergic activation influencing cardiovascular and body fluid homeostasis - Saad, Wilson Abrao; Guarda, Ismael Francisco Motta Siqueira; Camargo, Luis Antonio de Arruda; dos Santos, Talmir Augusto Faria Brisola; Saad, William Abrao (Elsevier B.V., 2007)
We have studied the effects of L-NG-nitro arginine methyl esther (L-NAME), L-arginine (LAR), inhibitor and a donating nitric oxide agent on the alterations of salivary flow, water intake, arterial blood pressure (MAP) and heart rate (HR) induced by the injection pilocarpine into the subfornical organ (SFO). Rats (Holtzman 250-300 g) were anesthetized with 2, 2, 2-tribromoethanol (20 mg/100 kg b. wt.) and a stainless steel carmula were implanted into their SFO. The volume of injection was 0.2 mu l. The amount of saliva secretion was studied over a 5-min period. Pilocarpine (40 mu g), L-NAME (40 mu g) and LAR (30 mu g) were used in all experiments for the injection into the SFO. Pilocarpine (10, 20, 40, 80 and 160 mu g) injected into SFO elicited a concentration-dependent increase in salivary secretion. L-NAME injected prior to pilocarpine into the SFO increased salivary secretion and water intake due to the effect of pilocarpine. LAR injected prior to pilocarpine into the SFO attenuated the salivary secretion and water intake. Pilocarpine, injected into the SFO increased the MAP and decreased heart rate (HR). L-NAME injected prior to pilocarpine into the SFO potentiated the pressor effect of pilocarpine with a decrease in HR. LAR injected into the SFO prior to pilocarpine attenuated the increase in MAP with no changes in HR. The present study suggests that the SFO nitrergic cells interfere in the cholinergic pathways implicated in the control of salivary secretion, fluid and cardiovascular homeostasis. (c) 2007 Elsevier B.V All rights reserved.
Keywords: pilocarpine; subfornical organ; nitric oxide; saliva; fluid and cardiovascular balance